A STUDY OF CLINICAL AND MICROBIOLOGICAL PROFILE OF VENTILATOR-ASSOCIATED PNEUMONIA AND HOSPITAL-ACQUIRED PNEUMONIA IN PATIENTS ADMITTED AT TERTIARY CARE CENTER - VIJAYALAKSHMI KP; SRIKANTH AK; KEERTI KEERTI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Ventilator-associated pneumonia (VAP) is a serious hospital-acquired infection that has a high death rate. The microbiological features of VAP have been the subject of only a few research conducted on small study populations in India. To evaluate the pathogen profile and identify the trend of antibiotic resistance, this study was conducted in the intensive care units (ICUs) of a tertiary care hospital. Methods: A prospective investigation of clinically suspected VAP cases was conducted. Our analysis included 247 instances with clinical evidence of VAP who were admitted to ICUs on mechanical ventilation over 1 year. After undergoing a quantitative culture procedure on the endotracheal aspirate samples from these probable cases, a colony count of ≥105 colony-forming units/mL was deemed significant. A test for the isolates’ susceptibility to antibiotics was conducted. Results: The incidence of VAP was more common in the elderly age group (45%) and predominated in males (57.5%) with a statistically insignificant p=0.3130. The majority of the patients were diagnosed with cerebrovascular accidents (41.25%). Poor outcome of VAP was associated with hypertension (51.25%) and diabetes mellitus (48.75%). Around 58 (72.5%) required intubation, and among the intubated, 29 (59.18%) showed improvement, and 29 (93.55%) patients died, with a significant p=0.0010. The majority of patients with VAP have demonstrated growth of Gram-negative organisms. Most of the Cefoperazone sensitive cases showed improvement (87.5%), with death in 12.5% cases, whereas the fatality rate was high in resistance cases (48.48%), which was statistically significant with a p=0.0140. Conclusion: The mortality incidence was higher in antibiotic-resistant cases than the sensitive cases. The incidence of VAP may be reduced by carefully selecting patients who need ventilator support.